THE IDEAS DEVELOPMENT OF ARGUMENTATIVE DISCOURSES OF INDONESIAN WRITERS FOUND IN THE OPINION FORUM OF THE JAKARTA POST - Dwi Rukmini, Katharina Abbas Achmad adib (Faculty of Humanities, Diponegoro University, 2012)
In this era, English is established as the world language of research and publication. This makes the English language significant for students and professionals. Tangkiengsirisin (2010, 1) states that text flow through a sequence of sentences is a main criterion for advanced writing. This research is aimed at finding out the flows of ideas of the English Arguments of Indonesian writers. This research applies topical, paradigmatic analysis. It involves identifying topics and sequences of topics/ ideas. After the topical analysis is done, the investigator contemplates the ideas development pattern of the entire essay. After analyzing fourteen English Arguments of Indonesian writers, it is found out that English Arguments of Indonesian writers are mostly developed linearly. It contradicts with Kaplan’s explanation (1966) that oriental groups express their ideas mostly in indirect ways. It means that at present Kaplan’s theory is partly valid. Even though the English Arguments of Indonesian writers are mostly developed linearly, it doesn’t mean that the teachers can ignore it in teaching Advanced Writing. Flow of ideas should become one of the materials of Advanced Writing to Indonesian learners, but it doesn’t need more teaching time allotment. Keywords: argumentative discourses, flow of ideas, linear, circular, parallel, digress